Numerical modeling of AAR - Saouma, Victor E. (CRC Press, 2014)
This reference book presents the theory and methodology to conduct a finite element assessment of concrete structures subjected to chemically induced volumetric expansion in general and alkali aggregate reaction in particular. It is limited to models developed by the author, and focuses on how to best address a simple question: if a structure suffers from AAR, how is its structural integrity jeopardized, and when would the reaction end. Subjects treated are: Brief overview of AAR: nature of the chemical reactions, AAR in both dams and nuclear power plants, and how does it impact the mechanical.